Analysis of E-Portfolio Assessment for Strengthening Disabled Students' Competencies in Central Lombok Primary Schools - Akhmad Muzakkir; Lalu Muazim; Baiq Luluk Hariyanti (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
The objective of this study is to ascertain the manner in which e-Portfolio assessment is implemented for students with disabilities in primary schools in Central Lombok Regency. Furthermore, it seeks to determine the efficacy of e-Portfolio assessment in enhancing the competencies of students with disabilities in primary schools in Central Lombok Regency. Finally, it explores how teachers and students perceive e-Portfolio assessment for students with disabilities in primary schools in Central Lombok Regency. The present study employed a mixed-methods approach, utilising a sequential explanatory design. The findings indicated that e-portfolios had a significant impact on students and led to the reconstruction of relationships within their ecosystem. The integration of the school microsystem and the family microsystem was facilitated by the provision of straightforward access for parents, thereby ensuring a harmonious alignment between the two systems. Secondly, a robust correlation has been identified between the implementation of e-portfolios and competency achievement, with a coefficient value of 0.990. This finding suggests that the more effective and consistent the implementation of e-portfolios is, the higher the competency achievement of students with disabilities. The correlation between the implementation of e-portfolios and the enhancement of student competencies, with a coefficient of 0.986, substantiates that efficacious e-portfolio practices directly contribute to the advancement and empowerment of the competencies of students with disabilities. The coefficient of 0.991 indicates that students who demonstrate high levels of competency achievement also tend to experience substantial improvement in their competencies. The strength of the relationship coefficient is.